Testing of models of stomatal ozone fluxes with field measurements in a mixed Mediterranean forest (Atmospheric Environment, 2013)
Mediterranean forests close to urban areas are exposed to polluted plumes loaded with tropospheric ozone. This is the case of Castelporziano Estate, a 6000 ha Mediterranean forest 25 km from Rome downtown on the coast of the Mediterranean Sea. In September 2011 we started an intensive ﬁeld campaign aimed at investigating ozone deposition from a mixed Mediterranean forest, mainly composed by Quercus suber, Quercus ilex, Pinus pinea. Measurements at canopy level with the eddy covariance technique were supported by a vegetation survey and the measurement of all environmental parameters which allowed to calculate stomatal ozone ﬂuxes. Leaf-level measurements were used to parameterize models to calculate stomatal conductance based on a Jarvis-type and BalleBerry approach. We show changes in magnitude of ozone ﬂuxes from a warm (September) to a cold period (OctobereDecember). Stomatal component explained almost the totality of ozone ﬂuxes during the cold days, but contributed only up to 50% to total ozone deposition during warm days, suggesting that other sinks (e.g. chemistry in the gas-phase) play a major role. Modeled stomatal ozone ﬂuxes based on a Jarvis-type approach (DO3SE) correlated with measured ﬂuxes better than using a BalleBerry approach. A third model based on a modiﬁed BalleBerry equation was proposed to account for the non-linear dependency of stomatal conductance on relative humidity. This research will help the development of metrics for ozone-risk assessment and advance our understanding of mixed Mediterranean forests in biosphereeatmosphere exchange.